The Effect of Growth Mindset and Basic Needs on Teacher's Performance Through Organizational Commitment - Fitri Nurjannah; Suwito Eko Pramono; Arief Yulianto (Universitas Negeri Semarang, 2026)
This research is prompted by the discrepancy between professional demands and the actual performance of teachers within the Darussalam Waqf Foundation, evidenced by a decline in the 2025 Education Report Card’s instructional quality scores. Although personal factors such as a growth mindset and the fulfillment of basic needs (physiological and safety) are considered crucial for enhancing pedagogical effectiveness, empirical evidence suggests that teacher performance has not yet reached optimal levels. This study aims to analyze the influence of growth mindset and basic needs on teacher performance, with organizational commitment positioned as a mediating variable hypothesized to strengthen emotional engagement and productivity. Utilizing a quantitative research approach, data were collected from 88 teachers across MI, MTs, MA, and SMK Darussalam Subah via structured questionnaires. This study employed path analysis and the Sobel test to evaluate both direct and indirect effects, alongside classical assumption testing to ensure data validity and reliability. The findings demonstrate that: 1) Growth mindset has a positive and significant effect on organizational commitment. 2) Basic needs have a positive and significant effect on organizational commitment. 3) Growth mindset has a positive and significant effect on teacher performance. 4) Basic needs have a positive and significant effect on teacher performance. 5) Organizational commitment has no significant effect on teacher performance. 6) Organizational commitment fails to mediate the influence of growth mindset on teacher performance. 7) Organizational commitment fails to mediate the influence of basic needs on teacher performance.